Expression analysis of inhibitor of apoptosis proteins (IAPs) and caspases in chick (Gallus gallus) neural retina embryonic development - Alrofidi, Aisha Abdullah (Trinity College (Dublin, Ireland). Department of Zoology, 2016)
Programmed cell death occurs naturally in developing neural tissues to regulate cell population, neural circuit connection and refined tissue structure. Caspases and inhibitor of apoptosis proteins (IAPs) are believed to contribute to the regulation of developmental cell death mechanisms by activating or inhibiting apoptosis. The molecular mechanism of apoptosis is still largely unidentified. This work aimed to characterise the temporal and spatial patterns of expression for all known embryonic chicken (Gallus gallus) IAP and caspase genes in the developing neural retina at both transcript and protein levels. In the developing retina of a chick embryo, two waves of cell death were reported by earlier studies between E4 and E16; early and late. Ten developmental stages ranging for early (embryonic day (E4) to late stage (E16) were investigated. Gene expression analysis was performed using PCR techniques. Subsequently, Western blotting (WB) and ELISA were used for investigation of protein temporal and spatial expression
Keywords: Zoology, Ph.D.; Ph.D. Trinity College Dublin, 2016